Penerapan Enkripsi dan Dekripsi Dokumen Data UMKM Menggunakan Algoritma ChaCha20-Poly1305 - Widjaya, I Made Chandra; Mogi, I Komang Ari (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
Despite the increasing importance of data security in safeguarding sensitive information, this study addresses the potential risks associated with unauthorized access to critical data. Employing the ChaCha20-Poly1305 algorithm, the research focuses on implementing encryption and decryption processes for Small and Medium Enterprise (SME) documents, supplemented by key derivation from AES-256 for enhanced security. A nonce Initialization Vector (IV) is generated using the ChaCha20-Poly1305 algorithm, with users inputting secret keys for encryption. The system then encrypts the data using the ChaCha-Poly1305 algorithm and derives keys from AES using SHA-256 hashing. For decryption, users input the encrypted document into the program, along with the previously used key. The system design employs a simple web-based application, with the ChaCha20-Poly1305 cryptography algorithm implemented in PHP. The study successfully tests the ChaCha20-Poly1305 algorithm and the program exhibits secure decryption processes, evidenced by consistent byte sizes of tested SME documents.